A View of the Problem of Cytomegalovirus Infection in Pregnant Women: Secondary Prevention with Valacyclovir and the Feasibility of Universal Serological Screening to Reduce the Risk of Neonatal Pathology - A. Zinchuk (Львівський клінічний вісник, 2024)
Introduction. Cytomegalovirus (CMV) infection is the most common perinatal infection worldwide, diagnosed in 0.5-1.3 % of newborns in various regions. Approximately 86.0 % of women of childbearing age are seropositive for CMV. While a substantial body of research has focused on developing methods for the etiotropic treatment of pregnant women with primary CMV infection to prevent neonatal disease (secondary prevention) and evaluating the feasibility of screening pregnant women for CMV, these aspects remain unclear and require further investigation.